Nurses’s Experience in Providing Spiritual Care - Nunung Rachmawati; Tenang Aristina (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Spiritual care is considered by nurses not as part of their duties and responsibilities, so that the spiritual needs of many patients are neglected. Spiritual care is a necessity that is often overlooked in daily nursing practice and is less a priority than physical needs because spiritual needs are often abstract, complex, and more difficult to measure. Objectives: This study aims to determine the description of the nursing experience of the “YKY” Nursing Academy alumni in providing spiritual care. Methods: This study uses a qualitative method with a phenomenological approach. The subjects in this study were the alumni nurses of the Nursing Academy "YKY" Yogyakarta who worked at Sleman Yogyakarta Hospital and fulfilled the participant criteria which were set as the characteristic limits in this study. Results: Based on the analysis results of the in-depth interviews, researchers identified five themes related to the purpose of the study, 1) The importance of nurses providing spiritual care to patients and their families 2) Forms of spiritual care provided by nurses to patients and patient’s families 3) Nurses' perceptions of spiritual care 4) Nurses in providing spiritual care to patients are influenced by internal and external factors 5) Spiritual care is given by all personnel in the hospital. Conclusion: Spiritual care is an important part of nursing provided to improve the quality of life of patients.